From Borderland to No-Man’s Land: The United States, Mexico, and Their Common Border since the End of the Cold War - N. Schubert, Frank (FOCUS: Papers in English Literary and Cultural Studies, 2006)
“Frontiers, borderlines, and frames” are issues that have been with us for millennia, not just in literature and the arts, but in the physical world in which we all live. They and the structures that mark them have been facts of human life since the first encounter between two tribes. Derek Williams, a distinguished historian of Roman frontiers claims that “walls” are as old as the idea of property. Fourteenth-century thinkers even conceived of the Garden of Eden as “cut off from the rest of the world by a great mountain or ocean barrier or fiery wall,” so the concept can even be said to date back to the biblical beginning of humankind (Tuchman 60). John Milton, in Paradise Lost (book VI, line 860), also alluded to a celestial wall, describing a “Chrystal wall of Heav’n” (139). Even today, in a period often characterized, perhaps mistakenly, by the word “globalization,” borders and walls remain a significant part of the landscape, artifacts reinforcing the dominant concept of the nation-state.